A Study the health Issues of Lactating Mothers (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Women's healthcare status is correlated with biological, social, & cultural aspects. Indian women are particularly susceptible during pregnancy and lactating. Lactating moms have unique dietary requirements due to the increased caloric and nutrient intake necessary for breastfeeding. This paper is focusing the health status and issues of lactating mothers. During lactation, the mother provides nearly as efficient nutrition to her infant as the placenta does while also safeguarding him or her. Lactating women should be wisely given nutritional supplements since they have the potential to boost the infant's nutrition intake by increasing the efficiency of lactation. A mother's consumption of all the nutrients is inadequate to meet her growing infant's demands in poor nations, according to recent discoveries. Lactation is the process by which a mother produces and secretes milk from her breasts for her newborn to consume.